MEMBENTUK KELUARGA SAKINAH MENURUT HADIS NABI SAW - Tasbih, Tasbih (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2015)
Happy family become the hope of all the Muslim family with the assumption that everyone has the ability to be a servant of God fearing. Creating an atmosphere of Vegas in the family is not merely the duty of a wife, but must be supported by both parties (husband and wife). Wife in a domestic role was merely around the globe, while childcare for creating a happy family is not just revolve around the issues around the globe, but good role models based on the teachings of Islam, which is played by both parents in a household can not be abandoned. That understanding was revealed to review some of the traditions in this paper.